Beinart, William y Colin Bundy, Hidden Struggles in Rural South Africa. Politics & Popular Movements in the Transkei & Eastern Cape, 1890-1930. Londres, James Curry LTD, 1987, 326 pp. - Fajer Flores, Ana Luisa (Estudios de Asia y África, 1988)
-